Analisis Keaktifan Bertanya Dalam Proses Pembelajaran Mahasiswa Semester VI Kelas A Program Studi Pendidikan Ekonomi Universitas Bhinneka PGRI Tulungagung Tahun 2025 - Kurniawan, Krisna Mahendra; Umami, Nailariza (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the level of students' questioning activity in the learning process and identify internal and external factors that influence it. The subjects of the study were sixth semester students of class A of the Economics Education Study Program, Bhinneka PGRI University, Tulungagung in 2025. The study used a qualitative descriptive approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study showed that students' questioning activity is still relatively low and has not become a deep-rooted learning culture. The dominant internal factors include low interest in the material, lack of self-confidence, and suboptimal learning motivation. Meanwhile, external factors include a less conducive classroom atmosphere, teaching methods that are not fully interactive, and peer influence. Lecturers have a strategic role in creating an inclusive learning climate through active methods such as Problem Based Learning, group discussions, and providing motivation and a safe space to ask questions. This study concludes that increasing students' questioning activity requires a comprehensive approach that includes psychological, pedagogical, and social aspects in the lecture environment.